Nano-Modified Titanium Implant Materials: A Way Toward Improved Antibacterial Properties - Liu, Jianqiao; Liu, Jia; Attarilar, Shokouh; Wang, Chong; Tamaddon, Maryam; Yang, Chengliang; Xie, Kegong; Yao, Jinguang; Wang, Liqiang; Liu, Chaozong; Tang, Yujin (Frontiers in Bioengineering and Biotechnology, 2020)
Titanium and its alloys have superb biocompatibility, low elastic modulus, and favorable corrosion resistance. These exceptional properties lead to its wide use as a medical implant material. Titanium itself does not have antibacterial properties, so bacteria can gather and adhere to its surface resulting infection issues occurrence. The infection is among the main reasons for implant failure in orthopedic surgeries. Nano-modification as one of the good options have the potential to induce different degrees of antibacterial effect on the surface of implant materials. At the same time, the nano-modification procedure and the produced nanostructures should not adversely affect the osteogenic activity and it should simultaneously lead to favorable antibacterial properties on the surface of the implant. This article scrutinizes and deals with the surface nano-modification of titanium implant materials from three aspects: nano-structure formation procedures, nanomaterials loading, and nano-morphology. In this regard, the research progress on the antibacterial properties of various surface nano-modification of titanium implant materials and the related procedures are introduced, and the new trends will be discussed in order to improve the related materials and methods.